Biological therapies for psoriasis: Adherence and outcome analysis from a clinical perspective. (5th March 2015) - Ross, Christopher; Marshman, Gillian; Grillo, Marianne; Stanford, Tyman
Abstract: We evaluated and compared patients' long‐term adherence to biological therapies in a real‐life clinical setting. Secondary aims included weight changes on biological therapy and reporting adverse effects. This prospective case‐note review included 58 patients, undergoing 84 treatment series including etanercept (21), adalimumab (24), infliximab (14) and ustekinumab (25). Patients' adherence was greatest with ustekinumab (being 6.7‐fold less likely to withdraw from treatment than etanercept, P  = 0.014), while the difference in treatment adherence of adalimumab and infliximab compared to etanercept was not statistically significant. Adalimumab and infliximab were associated with an increase in weight, while ustekinumab was associated with weight loss compared with etanercept (not statistically significant). Long‐term patient adherence to biologic therapy in patients with psoriasis is greatest with ustekinumab.